2011
DOI: 10.1007/s11434-011-4573-1
|View full text |Cite
|
Sign up to set email alerts
|

A palynological and palaeoclimatological record from the southern Philippines since the Last Glacial Maximum

Abstract: A palynological analysis of a marine sediment core in the southern Philippines, provides a detailed regional vegetation and climate history for the West Pacific Warm Pool (WPWP) since the Last Glacial Maximum (LGM). Chronology was determined by a detailed oxygen isotope record. A higher representation of pollen from tropical upper montane rainforest during the LGM indicate that this forest type moved down along elevation, probabaly due to the lowered temperature. During the last deglaciation and the early Holo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Additionally, increased silica input during periods of high discharge may result in blooms of predominantly siliceous phytoplankton [Weldeab et al, 2007], reducing productivity of calcareous species. This interpretation of log(Fe/Ca) records as an indicator of fluvial discharge is further supported by published pollen records from the same core [Bian et al, 2011] which suggest dry conditions during the LGM compared to the Holocene, as observed in our log(Fe/Ca) records, as well as reduced accumulation rates during the glacial portion of our record, which would be consistent with reduced sedimentary discharge. Taken together, our XRF log ratios and paleoproductivity reconstructions from the Davao Gulf present a robust picture of local rainfall variability over Mindanao during the past 120 ka.…”
Section: Proxies Of Sedimentary Dischargesupporting
confidence: 91%
“…Additionally, increased silica input during periods of high discharge may result in blooms of predominantly siliceous phytoplankton [Weldeab et al, 2007], reducing productivity of calcareous species. This interpretation of log(Fe/Ca) records as an indicator of fluvial discharge is further supported by published pollen records from the same core [Bian et al, 2011] which suggest dry conditions during the LGM compared to the Holocene, as observed in our log(Fe/Ca) records, as well as reduced accumulation rates during the glacial portion of our record, which would be consistent with reduced sedimentary discharge. Taken together, our XRF log ratios and paleoproductivity reconstructions from the Davao Gulf present a robust picture of local rainfall variability over Mindanao during the past 120 ka.…”
Section: Proxies Of Sedimentary Dischargesupporting
confidence: 91%
“…Another factor to be considered for the survival of Quaternary climatic changes by tropical lowland plants is competition with tropical montane plants, which descended to lowlands during cooler periods. In adjacent mountainous landmasses, namely, Taiwan Island with more than 200 peaks over 3000 m and the main islands of the Philippines with mountains below 3000 m in elevation, molecular and palynological studies have indicated altitudinal migration of montane plants during cooler periods (Hwang et al ., ; Shih et al ., ; Bian et al ., ; Nakamura et al ., ; Liew et al ., ). The islands of the present study are all low and lack montane vegetation.…”
Section: Discussionmentioning
confidence: 98%
“…A key obstacle in the interpretation of geochemical data from marine sediments as proxies for chemical weathering is to constrain their sources and the mechanism and strength of sediment transport processes because changes in provenance can affect these proxies and, thus, the environmental interpretation (Clift et al, ; Colin et al, ; Hu et al, ; Li et al, ; Wan et al, ; Xiong et al, ; Zheng et al, ). If the source can be constrained, then the sediment fluxes and transport processes involved can be related to continental weathering/erosion intensity and rates, mostly those associated with a monsoon climate (Bian et al, ; Cai et al, ; Chen et al, ; Clift et al, ; Wan et al, ; Xu et al, ; Zhao et al, ). We cannot assume that modern fluvial sediments are similar to older sediments because large changes have been recorded over glacial cycles (Clift et al, ), and over the past 5 Ma, there have been major changes in the isotope composition of the Indus River, originally linked to drainage reorganization (Clift & Blusztajn , ) but now argued to be linked to unroofing of new source regions (Chirouze et al, ).…”
Section: Discussionmentioning
confidence: 99%